Editorial - Cancino Izaguirre, Heli (2015)
The Peruvian Society of Obstetrics and Gynecology in 1977 meet the 50 years since its foundation. Date important to keep in mind and call us to a deep reflection What are being met with the likely purpose of its founding? I think when ginecoobstetras five decades ago had the bright idea of founding our Society to fight for the development and progress of this specialty, standardize the binomial mother-child care, other colleagues show achievements in the field, the discuss diagnostic and therapeutic procedures were trying to create a Peruvian school of our specialty, and that's due to the tenacious and sacrificing work of those who now exercise teaching, likely many students of our founders.